2018
DOI: 10.1101/437905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic metaanalyses of autistic brains reveals shared gene expression and biological pathway abnormalities with cancer

Abstract: Epidemiological and clinical evidence points to cancer as a comorbidity in people with autism spectrum disorders (ASD). A significant overlap of genes and biological processes between both diseases has also been reported. Here, for the first time, we compared the gene expression profiles of ASD frontal cortex tissues and 22 cancer types obtained by differential expression meta-analysis. Four cancer types (brain, thyroid, kidney, and pancreatic cancers) presented a significant overlap in gene expression deregul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…More recent studies have suggested that EPHB6 is a candidate ASD-associated gene [ 14 16 ], and recent genomic studies have found that EPHB6 is mutated in some ASD patients [ 17 , 18 ]. Most importantly, transcriptome analyses have shown that EPHB6 is downregulated in ASD patients [ 19 , 20 ]. Although EPHB6 plays an important role in regulating Eph receptor signaling networks, T cell functions, development of intestinal epithelium, and epithelial homeostasis [ 21 23 ], the role and mechanisms of EPHB6 involved in regulation of the gut microbiota and ASD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have suggested that EPHB6 is a candidate ASD-associated gene [ 14 16 ], and recent genomic studies have found that EPHB6 is mutated in some ASD patients [ 17 , 18 ]. Most importantly, transcriptome analyses have shown that EPHB6 is downregulated in ASD patients [ 19 , 20 ]. Although EPHB6 plays an important role in regulating Eph receptor signaling networks, T cell functions, development of intestinal epithelium, and epithelial homeostasis [ 21 23 ], the role and mechanisms of EPHB6 involved in regulation of the gut microbiota and ASD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that several candidate genes demonstrated differential expression of ASD patients in brain and blood, as compared to healthy controls [ 4 , 5 , 6 , 7 , 8 , 9 ]. Despite some important data having been obtained from previous analyses [ 4 , 10 ], we here applied a System Biology approach to further deepen the understanding of the pathophysiological mechanisms in ASD. In this study, two independent publicly available ASD brain studies were used to perform a meta-analysis aimed at identifying novel ASD candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…First in our study, we uncover EphB6 is an ASD-associated gene functionally. EPHB6 has been suggested as a candidate gene for ASD for a long time [15][16][17] and is found to be down-regulated in ASD patients [19,20]. Here, using our transgenic mouse models, we found deletion of EphB6 induced autism-like behavior in mice that mimicked the core symptoms of ASD patients fairly well.…”
Section: Discussionmentioning
confidence: 57%
“…After that, more studies suggested EPHB6 as a candidate of ASD-associated-gene [14][15][16] and recent genomic studies have found the mutation of EPHB6 in some ASD patients [17,18]. Most importantly, EPHB6 has been found to be with a down-regulated expression in ASD patients in transcriptome analysis [19,20]. Although EPHB6 plays an important role in regulating Eph receptor signaling networks, T cell functions, development of intestinal epithelium and epithelial homeostasis [21][22][23], the role and mechanisms of EPHB6 involved in regulating gut microbiota and ASD are still unclear.…”
mentioning
confidence: 99%